2021
DOI: 10.1038/s41522-021-00200-z
|View full text |Cite
|
Sign up to set email alerts
|

Treatment with a neutrophil elastase inhibitor and ofloxacin reduces P. aeruginosa burden in a mouse model of chronic suppurative otitis media

Abstract: Chronic suppurative otitis media (CSOM) is a widespread, debilitating problem with poorly understood immunology. Here, we assess the host response to middle ear infection over the course of a month post-infection in a mouse model of CSOM and in human subjects with the disease. Using multiparameter flow cytometry and a binomial generalized linear machine learning model, we identified Ly6G, a surface marker of mature neutrophils, as the most informative factor of host response driving disease in the CSOM mouse m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…Topical fluoroquinolones effectively convert active disease to inactive but, by mechanism, do not address persister cells, which are the key drivers of CSOM recurrence. 42-44 However, these findings are limited by possible selection bias, as patients at a tertiary center likely represent the more severe spectrum of disease. We aimed to account for this by not setting a minimum follow-up time for medical outcomes and analyzing if prior surgery influenced outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Topical fluoroquinolones effectively convert active disease to inactive but, by mechanism, do not address persister cells, which are the key drivers of CSOM recurrence. 42-44 However, these findings are limited by possible selection bias, as patients at a tertiary center likely represent the more severe spectrum of disease. We aimed to account for this by not setting a minimum follow-up time for medical outcomes and analyzing if prior surgery influenced outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, patients who were otorrhea free at the most recent visit had episodes of otorrhea at earlier visits and may develop recurrent otorrhea at future visits, suggesting even poorer results. Topical fluoroquinolones effectively convert active disease to inactive but, by mechanism, do not address persister cells, which are the key drivers of CSOM recurrence 42‐44 . However, these findings are limited by possible selection bias, as patients at a tertiary center likely represent the more severe spectrum of disease.…”
Section: Discussionmentioning
confidence: 99%
“…3C, D and S3). Ly6G + cell recruitment in the lungs, which is associated with neutrophil levels (37), was also measured, since neutrophils have been reported to serve an important role in lung injury (38). Immunohistochemical staining results indicated that the number of Ly6G + cells was significantly increased in the SAP group compared with in the Sham group, and this was then significantly decreased by emodin or DEX treatment (Fig.…”
Section: Emodin and Dex Decrease Apoptosis In The Lungs During Sap Progressionmentioning
confidence: 98%
“…Neutrophils are responsible for both host defense and host tissue damage in the early phase of bacterial infections particularly in CSOM [ 25 ]. We have previously identified that neutrophils were the most abundant cell type in CSOM middle ear effusions using Ly6G/C, a surface marker of mature neutrophils, by multi-parameter flow cytometry (FCM) analysis [ 25 ]. In the current study, we performed immunostaining with the Ly6G/C antibody to assess neutrophil presence in the cochlea.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, immune cell-mediated damage might explain our findings in this model of CSOM. We and others previously showed that CSOM contains a predominance of neutrophils in the middle ear [ 3 , 25 , 43 ]. This current study showed a paucity of neutrophils in the inner ear and the timing observing these neutrophils was not in keeping with the observed OHC loss, ruling this cell out as the main driver for SNHL in CSOM.…”
Section: Discussionmentioning
confidence: 99%